Professores ou Historiadores? O dilema da formação docente nos cursos de licenciatura em História de Cachoeiro de Itapemirim - ES - Oliveira, Thais Silva de (2021)
In reflecting on the dilemma between the specific and pedagogical knowledge in the training of history teachers, this dissertation seeks to understand what is the understanding of teachers who graduated in History, in institutions that offered and still o